A clinical score for prediction of elevated aortic stiffness: derivation and validation in 3943 hypertensive patients. Issue 2 (February 2019) - Xaplanteris, Panagiotis; Vlachopoulos, Charalambos; Protogerou, Athanasios D.; Aznaouridis, Konstantinos; Terentes-Printzios, Dimitrios; Argyris, Antonios A.; Tentolouris, Nikolaos; Sfikakis, Petros P.; Tousoulis, Dimitrios
Abstract : Objective: Aortic stiffness assessed by carotid–femoral pulse wave velocity (PWV) is an important predictor to gauge the overall risk of hypertensive patients; nonetheless, it is underutilized in everyday practice. We propose a simple scoring system based on clinical variables that can identify patients with a priority for measurement of PWV, that is, those with elevated PWV (≥10 m/s) and, consequently, at higher risk for events. Methods: Patient data from three outpatient clinics ( n = 3943) were used to form a derivation, internal and external validation cohort. For derivation, independent predictors of high PWV from a binary logistic regression model were split in subcategories and implemented in a simple clinical prediction scoring system with the acronym SAGE (office systolic blood pressure, age, glycemia and eGFR categories). Results: Its performance was validated at the internal and external validation cohorts with c -statistics being 0.83 (95% CI 0.81–0.86) and 0.77 (95% CI 0.73–0.80), respectively. A cut-off of eight points to identify patients with high PWV in the internal/external validation cohorts yielded a positive-predictive value, negative-predictive value, sensitivity and specificity of 52/36%, 88/81%, 56/70% and 88/65%, respectively. Conclusion: The SAGE score that takes into account easily measured clinical variables (office SBP, age, fasting glucose and eGFR categories) can be used to accurately predict elevated levels of PWV and prioritize its measurement in specific hypertensive patients. Its use will result in greater acknowledgement of the role of aortic stiffness and aid physicians in implementing it in clinical practice. Abstract : Supplemental Digital Content is available in the text